A Synthetic Phospholipid Derivative Mediates Ion Transport Across Lipid Bilayers - Wang, Chenxi; Yang, Huiting; Xiang, Yanxin; Pang, Shihao; Bao, Chunyan; Zhu, Linyong (Frontiers in Chemistry, 2021)
Inspired by the natural phospholipid structures for cell membrane, a synthetic phospholipid LC with an ionophore benzo-18-crown-6 (B18C6) moiety was prepared which has been demonstrated to be able to transport ions across the lipid bilayers. Fluorescent vesicle assay shows that LC has an excellent transport activity, and the EC50 value is 11.2 µM. By changing the cations outside the vesicles, LC has selectivity for Rb+ and Cs+, whose ionic radius are larger than that of the cavity of crown ether. It suggests that the sandwich interaction may play a key role in the ion transport across lipid bilayers. The voltage clamp measurement exhibits regular square-like current signals with considerably long opening times, which indicates that LC achieves efficient ion transport through a channel mechanism and its single channel conductivity is 17 pS. All these results help us to draw a conclusion that LC transports ions through the relay mechanism of a tetrameric aggregate. In addition, LC had obvious toxicity to HeLa cells, and the IC50 was 100.0 μM after coculture for 36 h. We hope that this simple synthetic phospholipid will offer novel perspectives in the development of more efficient and selective ion transporters.